Classroom Management Scripts: a Theoretical Model Contrasting Expert and Novice Teachers' Knowledge and Awareness of Classroom Events - Charlotte E. Wolff; Halszka Jarodzka; Henny P. A. Boshuizen (SPRINGER/PLENUM PUBLISHERS, 2022)
Dealing with the complexities of the classroom and the diversity of events in classroom situations presents a major challenge for classroom management. The knowledge a teacher has for processing this complexity depends a great deal on their level of experience, leading to differences in the way teachers perceive and interpret classroom events. This includes how they monitor events and how they maintain an ongoing awareness of classroom situations. It also impacts decisions about when and how to act in response to events. Research on classroom management has often focused on how to handle common classroom situations, but does not provide a theoretical description of how knowledge from experience affects teachers' awareness and ability to manage the classroom. This article proposes a definition forclassroom management scriptsby contrasting expert and novice teachers' knowledge and their decisions to act in response to classroom events. Classroom management scripts help clarify differences in teachers' recognition and representation of events by considering how expertise influences visual perception and mental interpretation. The proposed model exposes the internal cognitive processing involved in classroom management. Such insights can be useful for helping teacher educators and teachers themselves analyze and make sense of puzzling events. In turn, this may help develop training approaches to improve teachers' awareness of factors easily overlooked when considering classroom management, enhancing professional vision. This theory also underlines the centrality of facilitating and sustaining learning when grappling with the challenges of managing a classroom.